International Energy Transition: A Review of its Status on Several Continents - Vigoya, Marlen Fonseca; Mendoza, JosÃ© GarcÃa; Abril, Sofia Orjuela (International Journal of Energy Economics and Policy, 2020)
Many of the more developed countries and other members of the United Nations organization are already working hard on energy transition issues, which is nothing more than the independence of fossil energy sources and the technological foray into clean energy sources. This independence is generally achieved by replacing conventional energy sources with alternative renewable sources, and because of this, it is also necessary to adapt or replace systems using these conventional sources with systems using alternative sources. In the United States of America, they have set to work seeking to reduce dependence on oil and increasing the production of natural gas and biofuel, which will save eighteen hundred barrels of oil. In England, decarbonization and energy efficiency increase plans are carried out that proposes an 80% reduction in emissions. Likewise, efforts are made in the European Union to increase energy efficiency and renewable energy, as well as CO2 capture and nuclear energy generation, as well as cost reductions of all renewable energies of up to 53%. For its part, China represents almost half of the world’s investment in renewable energy in something they call the energy revolution, despite the fact that it has also been a major importer of oil. In Latin America, Brazil is aiming at decarbonization by designing adequate mechanisms and policies for sustained development in the use of renewable energy sources, in addition to increasing the use of solar electric power generation sources, among others. In this paper, you can find the efforts made and projections on energy transition in some countries. Keywords: Energy transition, Consumption Reduction, Energy Efficiency, Decarbonization, Renewable Sources. JEL Classifications: L78, L90, O31, Q20 DOI: https://doi.org/10.32479/ijeep.10116